The impact of geopolitical trends on modern banking business in Russia - E. A. Zolotova; E. Yu. Kalashnikova; D. Kh. Kottoeva; E. S. Nemtsova; O. N. Chuvilova (Вестник Северо-Кавказского федерального университета, 2023)
The consequences of the geopolitical crisis and «endless» sanctions affected the development of all sectors of the Russian economy, including the banking sector, which suffered a significant blow. The relevance of the article is due to the development of a set of solutions aimed at achieving the goals of «Russification» of modern banking business, but taking into account world standards. The aim of the study was to develop measures to prevent (up to leveling) the impact of sanctions and geopolitical restrictions on the banking business based on monitoring the current situation in the banking system, the quantitative and qualitative parameters of which are currently being formed. The scientific novelty of the work lies in the assessment of the influence of geopolitical trends on modern banking business. The methodological component includes an assessment of the change in the vector of banking services in modern conditions, a qualitative assessment of the problems of the banking business. As a result, measures are being developed to address these problems. The conclusion is made about the priority of evolving their own directions for the development of the banking business.